Low-temperature early-strength cement slurry system based on cellulose-based composite phase change materials

By using cellulose-based composite phase change materials, the problems of slow cement hydration speed and high hydration and heat release in low-temperature cementing wells are solved, and the early strength of cement and the regulation of hydration and heat release are achieved, which improves the cementing success rate.

CN119410345BActive Publication Date: 2025-04-04SOUTHWEST PETROLEUM UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510018761.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Cementing technology in low-temperature areas such as deep sea and polar regions faces problems such as slow cement hydration at low temperatures, difficulty in early strength development, and excessive hydration and exothermic heat dissociation leading to natural gas hydrate dissociation. The existing phase change materials have poor encapsulation, small latency heat, high cost and affect the mechanical properties of cement.

Method used

Using cellulose-based composite phase change material, by pretreating waste paper fibers and combining them with crosslinking agents and thermally conductive materials, a multi-dimensional heat transfer-enhanced composite phase change material is formed, and added to cement slurry to control hydration exothermic and early strength.

Benefits of technology

It achieves excellent temperature control capability within the range of 2-10℃, reduces the hydration heat release of cement, improves the early compressive strength of cement, solves the contradiction between reducing hydration heat and improving early strength, and enhances the cementing success rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410345B_ABST
    Figure CN119410345B_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature early-strength cement slurry system based on a cellulose-based composite phase change material, which belongs to the field of oil and gas field cementing. The composite phase change material is prepared as follows: pretreated waste paper fiber, a cross-linking agent, and a heat-conducting material are added to an alkali / urea solution, placed in an ultrasonic cleaning instrument, and a mixture A is obtained; it is transferred to a dialysis bag and soaked in deionized water to obtain a mixture B; it is mixed in situ with organic phase change material molecules to obtain a mixture C, and vacuum freeze-dried. The low-temperature early-strength cement slurry system is composed of the following components in parts by weight: 100 parts of cement, 0.3-1 parts of composite phase change materials, 5-25 parts of density reduction materials, 0.1-0.8 parts of early strength agents, 0.2-1 parts of dispersants, 0.2-2 parts of fluid loss reducing agents, 0.01-0.5 parts of defoaming agents, and 44-58 parts of water. While regulating the heat release of cement hydration, the present invention can improve the early compressive strength of cement, increase the timeliness of operation and construction safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oil and gas field cementing, and relates to a cement slurry system for low-temperature cementing, and in particular to a low-temperature early-strength cement slurry system based on a cellulose-based composite phase change material and its application in cementing engineering. Background Art

[0002] In recent years, as the exploration and development of the world's oil and gas resources has continued to evolve towards the deep sea, deep layers and unconventional, the development of global deep-sea oil and gas resources has achieved remarkable results, and overall it has shown the characteristics of more, deeper, more concentrated and more economical. Against this background, deep-sea oil and gas resources will become an important successor to the future global oil and gas resource market, and gradually become the frontier of the world's oil and gas. In the exploration and development of deep-sea oil and gas resources, cementing is an important link to ensure the effective exploitation of deep-sea oil and gas resources. Unlike conventional oil and gas production, the exploitation of deep-sea and polar oil and gas resources involves an energy substance that is very sensitive to both temperature and pressure - natural gas hydrates. The stability of natural gas hydrates on the seabed poses a huge challenge to cementing operations.

[0003] There are many urgent problems to be solved in cementing technology in low-temperature areas such as deep sea, ultra-deep sea and polar regions. On the one hand, facing the long-term low temperature of the seabed and the gradient of fracture pressure, the hydration speed of conventional oil well cement is slow, and it is difficult to quickly obtain early strength development, resulting in extended waiting time, increasing well construction costs and increasing the risk of water-gas channeling. On the other hand, since low-temperature early-strength cement slurry systems generally have high hydration heat, the large amount of heat released during the hydration process will increase the temperature around the wellbore and cause the surrounding natural gas hydrates to dissociate. The high-pressure free gas and water generated by the short-term decomposition of hydrates will enter the interior of the cement slurry, destroying the sealing integrity of the cement ring, and easily leading to cementing construction accidents such as well diameter expansion, blowouts and well kicks.

[0004] Phase change energy storage technology is an effective method to control the hydration heat and hydration temperature rise of cement. There are many phase change materials for building cement, but the leakage problem of solid-liquid organic phase change materials greatly affects the stability of the heat storage system and the safety of cement-based materials. Therefore, phase change materials are rarely used in low-temperature cementing slurries in deep sea and polar regions.

[0005] Phase change materials used to control the heat of cement hydration under low temperature conditions are mainly microencapsulated and encapsulated in porous media. "Hydrophilic paraffin microcapsule early strength low hydration exothermic cement system" (CN105733519A) uses paraffin as the core material, methyl methacrylate as the shell material, benzoyl peroxide and divinylbenzene as hydrophobic cross-linking monomers, and uses the suspension polymerization method to prepare hydrophilic phase change microcapsules. Adding this microcapsule to cement slurry can significantly reduce the heat of cement hydration; "Cement-based phase change material and preparation method thereof" (CN117263623A) uses methyl laurate as the phase change energy storage material, modified sepiolite fiber as the encapsulation material, and ethyl cellulose and sodium silicate as the encapsulation film, which can effectively prevent the leakage of liquid phase change materials. Its phase change peak and phase change latent heat are -4.21°C and 77.75°C, respectively. J / g; "A phase-change encapsulated microsphere, early-strength low-hydration hot cement system and its application" (CN116803938A), using alkane materials distributed inside the core material carrier, epoxy resin coated on the surface of the core material carrier, can reduce the maximum hydration temperature rise of cement slurry by 22.8°C. Phase-change energy storage materials and technologies used in cement slurry currently have the following problems:

[0006] (1) The preparation process of microencapsulated phase change materials is complex, the thermal conductivity is poor, and the latent heat of phase change is small;

[0007] (2) The porous medium encapsulation technology has poor encapsulation performance for phase change materials with low phase change temperature (<25°C), and there will be a large leakage problem during the phase change process. The use of organic encapsulation will affect the mechanical properties of cement.

[0008] (3) The organic shell-coated phase change material has a low latent heat value and needs to be added in large quantities to achieve the regulation of the hydration heat release of low-temperature cement slurry, which not only increases the cost but also affects the mechanical properties of the cement slurry.

[0009] (4) There is a contradiction between reducing the hydration heat and increasing the strength of cement paste. For cementing deep-sea hydrate layers, preventing the hydrate layer from decomposing due to heat requires reducing the hydration heat of cement slurry. However, reducing the hydration heat will affect the compressive strength of cement paste. Summary of the invention

[0010] The purpose of the present invention is to provide a cellulose-based composite phase change material, which has stable shape, low phase change temperature, good compatibility, and solves the problems of low encapsulation rate, poor thermal conductivity, and phase change core material leakage that limit the heat storage / release of phase change materials, and can be used in 2-10°C cementing cement systems. At the same time, the raw material cost is low, the preparation method is simple, the environment is friendly, the performance is excellent, and it has broad market application prospects.

[0011] Another object of the present invention is to provide a low-temperature early-strength cement slurry system based on a cellulose-based composite phase change material. The cement slurry system overcomes the contradiction between reducing the hydration heat and improving the early strength of the cement slurry under low-temperature conditions by adding the cellulose-based composite phase change material, thereby achieving the improvement of the early compressive strength of the cement while regulating the heat release of cement hydration, thereby increasing the operation timeliness and construction safety, and greatly improving the success rate of cementing.

[0012] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0013] A cellulose-based composite phase change material is prepared by the following steps:

[0014] S1, deinking waste paper in a sodium hydroxide solution and oxidizing waste paper in a sodium hypochlorite solution to obtain pretreated waste paper fibers;

[0015] S2, adding the pretreated waste paper fiber, cross-linking agent and thermal conductive material into 50 mL of pre-cooled alkali / urea solution in a mass ratio of 2-6:0.2-0.8:0.5-4, stirring at 5°C for 10-30 min, and then placing in an ultrasonic cleaner for 30 min to obtain a mixture A;

[0016] S3, transfer mixture A to a dialysis bag, soak it in deionized water to obtain mixture B, and freeze it in a refrigerator;

[0017] S4, in situ mixing the frozen mixture B with the low-temperature organic phase change material molecules at a mass ratio of 1:0.5-3 to obtain a mixture C, and then washing the mixture C with ethanol and deionized water respectively;

[0018] S5. The mixture C from which impurities have been removed is freeze-dried under vacuum, and crushed to obtain a cellulose-based composite phase change material.

[0019] In step S1, the concentration of the sodium hydroxide solution in the deinking treatment is 0.75-1.5 mol / L, the treatment temperature is 60-90 °C, and the treatment time is 0.5-2 h; the concentration of the sodium hypochlorite solution in the oxidation treatment is 1.2-2.4 mol / L, the treatment temperature is 75 °C, and the treatment time is 1-3 h.

[0020] In step S2, the alkali / urea solution is prepared by mixing lithium hydroxide, urea, and H2O in a mass ratio of 5-7:12-16:77-83, and precooling at -12°C for 12 h.

[0021] In step S2, the cross-linking agent is one or more of N,N-methylenebisacrylamide, citric acid, and boric acid; and the thermal conductive material is one or more of graphite, hydroxylated carbon nanotubes, and boron nitride.

[0022] In step S3, the molecular weight cutoff of the dialysis bag is 8000, and the dialysis time is 6 to 12 h.

[0023] In step S4, the low-temperature organic phase change material molecules are one or more of tetradecanol, hexadecane, and dodecanol.

[0024] In the step S5, vacuum freeze drying is performed at -55°C for 72 to 96 hours to obtain a cellulose-based composite phase change material.

[0025] The low-temperature early-strength cement slurry system based on cellulose-based composite phase change material is composed of the following components in parts by weight: 100 parts of cement, 0.3-1 parts of cellulose-based composite phase change material, 5-25 parts of density reducing material, 0.1-0.8 parts of early strength agent, 0.2-1 parts of dispersant, 0.2-2 parts of fluid loss reducer, 0.01-0.5 parts of defoaming agent, and 44-58 parts of water.

[0026] The cement is a mixture of Class G oil well cement and sulphoaluminate cement.

[0027] The density reducing material, early strength agent, dispersant, fluid loss reducer and defoamer are all conventional additives used in cementing in oil and gas fields.

[0028] The density reducing material is one or more of hollow glass microspheres and expanded perlite.

[0029] The early strength agent is one or more of nano silicon dioxide, anhydrous sodium sulfate and sodium metaaluminate.

[0030] The dispersant is calcium lignin sulfonate or sulfonated melamine formaldehyde resin.

[0031] The fluid loss reducing agent is hydroxypropyl cellulose or sulfonated polyethylene toluene.

[0032] The defoaming agent is tributyl phosphate or glycerol polyether.

[0033] The reaction process and mechanism of action of the cellulose-based composite phase change material are as follows:

[0034] Waste paper forms a stable cellulose solution under the action of alkali / urea mixed solution and cross-linking agent. The pretreated fiber is immersed in the pre-cooled alkali / urea solvent (cellulose dissolving agent) to obtain a better swelling and dissolution effect. This is because the small molecules formed by alkali / urea hydrates and cellulose macromolecules dynamically self-assemble at low temperature to form hydrogen bond ligands. The hydroxide ions of the hydrate can react with the hydroxyl groups on the cellulose to destroy the hydrogen bonds within and between the cellulose molecules, change the cellulose crystal form, and dissolve into the solvent. At this time, the urea hydrate forms a pipeline inclusion complex in the outer layer of the cellulose complex to prevent the cellulose molecules from self-aggregating. Under the action of the cross-linking agent and the multi-dimensional thermal conductive material, it is more conducive to the formation of a dense fiber cross-linking network with enhanced heat transfer, and also improves the capacity of the phase change material. After adding the composite organic compound, the organic phase change material molecules are directly embedded in the thermal conductive network structure through mechanical stirring and ultrasonic dispersion. This physical action will maximize the latent heat of phase change. At the same time, the heat can be effectively transferred from the multi-dimensional heat transfer structure, which accelerates the thermal conduction speed of the overall material. The prepared cellulose-based composite phase change material is added to the prepared cement slurry. Within the limited temperature range of the material phase change, the melting and solidification of the cellulose-based composite phase change material is used to absorb or release heat to control the hydration temperature rise and total heat release of the cement slurry.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention provides a multi-dimensional heat transfer enhanced, waste paper cellulose-based composite phase change material. The shape-stable composite phase change material is obtained by pre-treating waste paper fibers and in-situ loading of multiple organic phase change material molecules. The phase change latent heat can reach 155.4 J / g and has excellent temperature control capability within the service temperature range of 2-10°C.

[0037] (2) In the preparation process of the cellulose-based composite phase change material, the solvent used is green and environmentally friendly, can efficiently dissolve fibers, and makes the fiber structure dense and has good thermal stability. The obtained composite phase change material has stable shape and good encapsulation;

[0038] (3) The cellulose-based composite phase change material has high phase change latent heat, excellent heat transfer performance and low phase change temperature. When added to cement slurry, a low dosage can achieve the target effect. When the cement slurry heats up rapidly after the induction period, the phase change material added to the cement slurry absorbs heat through solid-liquid phase change, reducing the heat released by cement hydration. When the cement hydration temperature is lower than the phase change temperature of the phase change material, the composite phase change material releases heat through phase change, promoting cement hydration and improving the early strength of cement, thus solving the contradiction between reducing the heat of cement hydration and improving the early strength.

[0039] (4) The cellulose-based composite phase change material uses waste paper as raw material, realizes resource utilization of waste, and has the advantages of reducing costs and increasing efficiency. Its raw material cost is low, the preparation method is simple, and it is environmentally friendly, which is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a microscopic morphology of the composite phase change material prepared in Example 1.

[0041] Figure 2 This is a microscopic morphology of the composite phase change material prepared in Example 4.

[0042] Figure 3 This is the differential scanning calorimetry (DSC) curve:

[0043] (a) is a pure phase change core material of hexadecane and dodecanol mixed in a ratio of 1:1; (b) is a composite phase change material prepared in Example 4.

[0044] Figure 4 The hydration heat release results of the blank cement slurry measured at 4 °C and 8 °C for the comparative example.

[0045] Figure 5 The hydration heat release results of the cement slurry added with the composite phase change material in Example 4 were measured at 4°C and 8°C. DETAILED DESCRIPTION

[0046] The present invention is further described below with reference to the accompanying drawings and examples, so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific embodiments, and for those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, they are all protected.

[0047] Unless otherwise specified, the materials, reagents, etc. used in the examples of the present invention can be obtained from commercial sources.

[0048] 1. Preparation of low-temperature early-strength cement slurry system based on cellulose-based composite phase change materials.

[0049] Example 1

[0050] A cellulose-based composite phase change material is prepared by the following steps:

[0051] (1) Pretreatment of waste paper: Weigh 10 g of shredded office waste paper and add it to a three-necked beaker together with a 0.75 mol / L sodium hydroxide solution, keep it heated in a water bath at 60°C, stir it at a speed of 2000 rpm for 0.5 h, wash and dry it, and then stir it in a 1.2 mol / L hypochlorous acid solution at 75°C at a speed of 2000 rpm for 1 h. After washing and drying, the pretreated waste paper fibers were obtained;

[0052] (2) Dissolution process: Lithium hydroxide, urea, and H2O were prepared in a mass ratio of 5:12:83 and precooled. 2 g of waste paper fiber, 0.2 g of N,N-methylenebisacrylamide, and 0.5 g of graphite obtained above were added to 50 mL of precooled alkali / urea mixed solution, magnetically stirred for 10 min, then ultrasonically treated and dialyzed at room temperature for 6 h to obtain a gel;

[0053] (3) Preparation of composite phase change material: The frozen gel-like substance and hexadecane were mixed in situ at a mass ratio of 1:1, and then washed and freeze-dried.

[0054] Preparation of low temperature early strength cement slurry system:

[0055] Weigh 50 parts of G-grade oil well cement, 50 parts of sulphoaluminate cement, 0.3 parts of cellulose-based composite phase change material, 8 parts of hollow glass microspheres, 0.1 parts of sodium aluminate, 0.3 parts of calcium lignin sulfonate, and 0.4 parts of hydroxypropyl cellulose as a dry powder mixture, measure 48 parts of water, and dissolve 0.05 parts of tributyl phosphate in water. Put the aqueous solution in a high-speed stirrer, rotate the stirrer at a low speed (4000±200 rpm), and add the weighed dry powder mixture within 15 seconds. Cover the stirrer with a lid and continue stirring at a high speed (12000±500 rpm) for 35 seconds to obtain a low-temperature early-strength cement slurry system.

[0056] Example 2

[0057] A cellulose-based composite phase change material is prepared by the following steps:

[0058] (1) Pretreatment of waste paper: Weigh 10 g of shredded office waste paper and add it to a three-necked beaker together with 1 mol / L sodium hydroxide solution, keep it heated in a water bath at 70 °C, stir it at 2000 rpm for 1 h, wash and dry it, then stir it in a 1.6 mol / L hypochlorous acid solution at 75 °C at 2000 rpm for 2 h, wash and dry it, and obtain the pretreated waste paper fibers;

[0059] (2) Dissolution process: Lithium hydroxide, urea, and H2O were prepared in a mass ratio of 6:14:80 and precooled. 4 g of waste paper fiber, 0.4 g of N,N-methylenebisacrylamide, and 1 g of hydroxylated carbon nanotubes were added to 50 mL of precooled alkali / urea mixed solution, magnetically stirred for 20 min, then ultrasonically treated and dialyzed at room temperature for 8 h to obtain a gel;

[0060] (3) Preparation of composite phase change material: The frozen gel, tetradecanol and hexadecane were mixed in situ at a mass ratio of 1:0.8:0.8, and then washed and freeze-dried.

[0061] Preparation of low temperature early strength cement slurry system:

[0062] Weigh 50 parts of G-grade oil well cement, 50 parts of sulphoaluminate cement, 0.5 parts of cellulose-based composite phase change material, 8 parts of expanded perlite, 0.2 parts of anhydrous sodium sulfate, 0.3 parts of sulfonated melamine formaldehyde resin, and 0.4 parts of sulfonated polyethylene toluene as a dry powder mixture, measure 48 parts of water, and dissolve 0.1 parts of tributyl phosphate in water. Put the aqueous solution in a high-speed stirrer, rotate the stirrer at a low speed (4000±200 rpm), and add the weighed dry powder mixture within 15 seconds. Cover the stirrer with a lid and continue stirring at a high speed (12000±500 rpm) for 35 seconds to obtain a low-temperature early-strength cement slurry system.

[0063] Example 3

[0064] A cellulose-based composite phase change material is prepared by the following steps:

[0065] (1) Pretreatment of waste paper: Weigh 10 g of shredded office waste paper and add it to a three-necked beaker together with a 1.25 mol / L sodium hydroxide solution, keep heating at 80 °C in a water bath, stir at 2000 rpm for 1.5 h, wash and dry, then stir in a 2 mol / L hypochlorous acid solution at 75 °C at 2000 rpm for 2.5 h, wash and dry to obtain pretreated waste paper fibers;

[0066] (2) Dissolution process: Lithium hydroxide, urea, and H2O were prepared in a mass ratio of 6:14:80 and precooled. 5 g of waste paper fiber, 0.6 g of N,N-methylenebisacrylamide, and 1 g of boron nitride were added to 50 mL of precooled alkali / urea mixed solution, magnetically stirred for 30 min, ultrasonically treated, and dialyzed at room temperature for 10 h to obtain a gel;

[0067] (3) Preparation of composite phase change material: The frozen gel, tetradecanol and dodecanol were mixed in situ at a mass ratio of 1:1:1, and then washed and freeze-dried.

[0068] Preparation of low temperature early strength cement slurry system:

[0069] Weigh 50 parts of G-grade oil well cement, 50 parts of sulphoaluminate cement, 0.7 parts of cellulose-based composite phase change material, 6 parts of hollow glass microspheres, 6 parts of expanded perlite, 0.4 parts of nano-silicon dioxide, 0.5 parts of calcium lignin sulfonate, and 0.7 parts of sulfonated polyethylene toluene as a dry powder mixture, measure 52 parts of water, and dissolve 0.15 parts of glycerol polyether in water. Put the aqueous solution in a high-speed stirrer, rotate the stirrer at a low speed (4000±200 rpm), and add the weighed dry powder mixture within 15 seconds. Cover the stirrer with a lid and continue stirring at a high speed (12000±500 rpm) for 35 seconds to obtain a low-temperature early-strength cement slurry system.

[0070] Example 4

[0071] A low-temperature cementing cellulose-based composite phase change material is prepared by the following steps:

[0072] (1) Pretreatment of waste paper: Weigh 10 g of shredded office waste paper and add it to a three-necked beaker together with a 1.5 mol / L sodium hydroxide solution. Heat it in a water bath at 90 °C and stir it at 2000 rpm for 2 h. After washing and drying, stir it in a 2.4 mol / L hypochlorous acid solution at 75 °C at 2000 rpm for 3 h. Wash and dry it to obtain pretreated waste paper fibers.

[0073] (2) Dissolution process: Lithium hydroxide, urea, and H2O were prepared in a mass ratio of 7:16:77 and precooled. 6 g of waste paper fiber, 0.8 g of N,N-methylenebisacrylamide, 0.5 g of hydroxylated carbon nanotubes, and 1 g of boron nitride were added to the precooled alkali / urea mixed solution, magnetically stirred for 90 min, then ultrasonically treated and dialyzed at room temperature for 12 h to obtain a gel;

[0074] (3) Preparation of composite phase change material: The frozen gel, hexadecane and dodecanol were mixed in situ at a mass ratio of 1:1.2:1.2, and then washed and freeze-dried.

[0075] Preparation of low temperature early strength cement slurry system:

[0076] Weigh 50 parts of G-grade oil well cement, 50 parts of sulphoaluminate cement, 0.9 parts of cellulose-based composite phase change material, 8 parts of hollow glass microspheres, 8 parts of expanded perlite, 0.2 parts of nano-silicon dioxide, 0.2 parts of anhydrous sodium sulfate, 0.6 parts of sulfonated melamine formaldehyde resin, and 0.8 parts of hydroxypropyl cellulose as a dry powder mixture, measure 54 parts of water, and dissolve 0.2 parts of glycerol polyether in water. Put the aqueous solution in a high-speed stirrer, rotate the stirrer at a low speed (4000±200 rpm), and add the weighed dry powder mixture within 15 seconds. Cover the stirrer with a lid and continue stirring at a high speed (12000±500 rpm) for 35 seconds to obtain a low-temperature early-strength cement slurry system.

[0077] 2. Performance analysis of low-temperature early-strength cement slurry system based on cellulose-based composite phase change materials

[0078] Preparation of blank cement slurry system (comparative example):

[0079] Weigh 50 parts of G-grade oil well cement, 50 parts of sulphoaluminate cement, 8 parts of hollow glass microspheres, 0.4 parts of nano-silicon dioxide, 0.2 parts of calcium lignin sulfonate, and 0.2 parts of hydroxypropyl cellulose as a dry powder mixture, measure 44 parts of water, and dissolve 0.01 parts of tributyl phosphate in water. Put the aqueous solution in a high-speed stirrer, rotate the stirrer at a low speed (4000±200 rpm), and add the weighed dry powder mixture within 15 seconds. Cover the stirrer with a lid and continue stirring at a high speed (12000±500 rpm) for 35 seconds to obtain a blank cement slurry system.

[0080] Depend on Figure 1 and Figure 2 It can be seen that the composite phase change material with a high content of phase change core material in the in-situ prepared composite phase change material has a stable shape, a smooth surface and good coating properties.

[0081] Depend on Figure 3 It can be seen that Figure (a) shows that the phase change temperature and latent heat of the pure phase change core material of a 1:1 mixture of hexadecane and dodecanol during the melting process are 17.64°C and 189.04J / g, respectively, and the phase change temperature and latent heat of the crystallization process are 10.73°C and 195.78J / g, respectively; the phase change temperature and latent heat of the composite phase change material (b) prepared in Example 4 during the melting process are 26.36°C and 158.75J / g, respectively, and the phase change temperature and latent heat of the crystallization process are 9.33°C and 153.41J / g, respectively, and the phase change enthalpy value is retained by 83.9%.

[0082] Depend on Figure 4 and Figure 5 It is known that under 4°C and 8°C curing, compared with the control group, the cellulose-based composite phase change material prepared in Example 4 can reduce the hydration temperature rise of the cement paste by 27.93% and 26.23%, respectively.

[0083] Cement slurry and cement paste were prepared according to GB / T 19139~2012 Test Methods for Oil Well Cement. The early compressive strength and hydration heat release of cement paste at 12h, 24h and 48h under 4°C curing were measured. The results are shown in Table 1.

[0084]

[0085] Table 1 shows the compressive strength test results of the cement slurry systems prepared in the comparative example and Examples 1-4 at 4°C and 8°C, after water bath curing for 24 hours and 48 hours. It can be seen from Table 1 that compared with the comparative example, at a curing temperature of 4°C, the compressive strength after curing for 24 hours can be increased by up to 25.08%, and the compressive strength after curing for 48 hours can be increased by up to 39.3%. At a curing temperature of 8°C, the compressive strength after curing for 24 hours can be increased by up to 22.01%, and the compressive strength after curing for 48 hours can be increased by up to 30.0%. The strength of cement paste is higher under 4°C curing because lower temperatures will cause the phase change material to release more heat, thereby promoting cement hydration and improving the 48h strength of cement paste.

Claims

1. A cellulose-based composite phase change material for a low-temperature early-strength cement slurry system is prepared by the following steps: S1, deinking waste paper in a sodium hydroxide solution and oxidizing waste paper in a sodium hypochlorite solution to obtain pretreated waste paper fibers; S2, adding the pretreated waste paper fibers, the cross-linking agent, and the thermal conductive material to the pre-cooled alkali / urea solution, stirring at 5°C for 10-30 min, and then placing in an ultrasonic cleaner for 30 min to obtain a mixture A, wherein the cross-linking agent is N,N-methylenebisacrylamide, and the thermal conductive material is one or more of hydroxylated carbon nanotubes and boron nitride; S3, transfer mixture A to a dialysis bag, soak it in deionized water to obtain mixture B, and freeze it in a refrigerator; S4, in situ mixing the frozen mixture B with low-temperature organic phase change material molecules to obtain a mixture C, and then washing the mixture C with ethanol and deionized water respectively, wherein the low-temperature organic phase change material molecules are one or more of tetradecanol, hexadecane, and dodecanol; S5. The mixture C from which impurities have been removed is freeze-dried under vacuum, and crushed to obtain a cellulose-based composite phase change material.

2. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution in the deinking treatment is 0.75-1.5 mol / L, the treatment temperature is 60-90 °C, and the treatment time is 0.5-2 h; the concentration of the sodium hypochlorite solution in the oxidation treatment is 1.2-2.4 mol / L, the treatment temperature is 75 °C, and the treatment time is 1-3 h.

3. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In step S2, the alkali / urea solution is prepared by mixing lithium hydroxide, urea, and H2O in a mass ratio of 5-7:12-16:77-83, and precooling at -12°C for 12 h.

4. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In the step S2, the mass ratio of the pretreated waste paper fibers, the cross-linking agent, and the thermal conductive material is 2-6:0.2-0.8:0.5-4, and they are added to 50 mL of the pre-cooled alkali / urea solution.

5. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In step S3, the molecular weight cutoff of the dialysis bag is 8000, and the dialysis time is 6 to 12 h.

6. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In the step S4, the mass ratio of the frozen mixture B to the low-temperature organic phase change material molecules is 1:0.5-3.

7. The cellulose-based composite phase change material for low-temperature early-strength cement slurry system according to claim 1, characterized in that: In the step S5, vacuum freeze drying is performed at -55°C for 72 to 96 hours to obtain a cellulose-based composite phase change material.

8. The low-temperature early-strength cement slurry system based on the cellulose-based composite phase change material according to claim 1, 2, 3, 4, 5, 6 or 7 is composed of the following components in parts by weight: 100 parts of cement, 0.3~1 parts of cellulose-based composite phase change material, 5~25 parts of density reducing material, 0.1~0.8 parts of early strength agent, 0.2~1 parts of dispersant, 0.2~2 parts of fluid loss reducer, 0.01~0.5 parts of defoaming agent, and 44~58 parts of water.

9. The low-temperature early-strength cement slurry system according to claim 8, characterized in that: The cement is a mixture of Class G oil well cement and sulphoaluminate cement.

10. The low-temperature early-strength cement slurry system according to claim 8, characterized in that: The density reducing material is one or more of hollow glass microspheres and expanded perlite; the early strength agent is one or more of nano-silicon dioxide, anhydrous sodium sulfate, and sodium aluminate; the dispersant is calcium lignin sulfonate or sulfonated melamine formaldehyde resin; the fluid loss reducer is hydroxypropyl cellulose or sulfonated polyethylene toluene; and the defoaming agent is tributyl phosphate or glycerol polyether.

Citation Information

Patent Citations

  • Hydrophilia paraffin microcapsule and early-strength low-hydration-heat-releasing cement system

    CN105733519A

  • Phase-change encapsulated microsphere, early-strength low-hydration-heat cement system and application of phase-change encapsulated microsphere and early-strength low-hydration-heat cement system

    CN116803938A

  • Cement-based phase change material and preparation method thereof

    CN117263623A

  • Early-strength low-hydration heat evolution cement paste system applicable to deepwater shallow cementation

    CN105802596A

  • Method for preparing cellulose composite aerogel from waste paper

    CN108484962A